Organisational scapegoats and hierarchical constraints : a critical discourse analysis of inter-agency collaboration within New Zealand's public sector : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy (Humanities and Social Sciences) in Defence and Security Studies at Massey University, Manawatu , New Zealand - Butler, Rachel (Massey University, 2015)
The legacy of the 2000s whole-of-government reform agenda promotes that public sector agencies work across the sector, encouraging an inter-agency collaborative approach to resolve the so called ‘wicked problems’ facing New Zealand. The initial 1980s public service reform agenda, established on a neoliberal philosophy, afforded greater decision-making autonomy to public servants and hierarchical simplification. Yet the author’s experience of inter-agency collaboration as a mid-level public sector official is that, despite best intentions, it is difficult in practice due to the paradoxical requirement of autonomous decision-making power and obligation to individual departments and their Chief Executives. These paradoxes manifest as tensions between the collaborative causal powers (agency) of public servants and the structure and practices of New Zealand’s Westminster system of governance that remains palpably hierarchical. This research uses Critical Discourse Analysis (CDA) as a methodological means of validating this hypothesis within the context of a case study of the National Maritime Coordination Centre. This theoretically driven research presents CDA as an alternative and instructive lens that provides an enhanced understanding of the real world issues associated with collaboration within New Zealand’s public sector to present possibilities for change.